2013
DOI: 10.1063/1.4790191
|View full text |Cite
|
Sign up to set email alerts
|

Shrink-induced sorting using integrated nanoscale magnetic traps

Abstract: We present a plastic microfluidic device with integrated nanoscale magnetic traps (NSMTs) that separates magnetic from non-magnetic beads with high purity and throughput, and unprecedented enrichments. Numerical simulations indicate significantly higher localized magnetic field gradients than previously reported. We demonstrated >20 000-fold enrichment for 0.001% magnetic bead mixtures. Since we achieve high purity at all flow-rates tested, this is a robust, rapid, portable, and simple solution to sort target … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
26
0

Year Published

2013
2013
2018
2018

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 25 publications
(26 citation statements)
references
References 23 publications
(26 reference statements)
0
26
0
Order By: Relevance
“…This is important to achieve large fluorescence enhancements in other regions of the excitation wavelength spectrum. We have also recently demonstrated that our Ni structures can generate strong localized magnetic gradients to serve as effective nanotraps for capture and separation [42]. Combining this utility with the large signal enhancements demonstrated here can pave the way to create a comprehensive integrated device to readily magnetically trap and sensitively detect labeled molecules and nanoparticles.…”
Section: Discussionmentioning
confidence: 80%
See 2 more Smart Citations
“…This is important to achieve large fluorescence enhancements in other regions of the excitation wavelength spectrum. We have also recently demonstrated that our Ni structures can generate strong localized magnetic gradients to serve as effective nanotraps for capture and separation [42]. Combining this utility with the large signal enhancements demonstrated here can pave the way to create a comprehensive integrated device to readily magnetically trap and sensitively detect labeled molecules and nanoparticles.…”
Section: Discussionmentioning
confidence: 80%
“…Recently, we demonstrated that with a very thin layer of Ni, effective ferro-magnetic nanotraps that localize strong magnetic fields can be formed with these wrinkles [42]. We found that increasing the Ni thickness to 30 nm increased the size and reduced the sharpness of the nanowrinkles and as a result decreased the magnetic strength.…”
Section: Fabrication and Characterization Of Composite Structuresmentioning
confidence: 95%
See 1 more Smart Citation
“…Obviating photolithography enables devices to be fabricated that are larger, three-dimensional, inexpensive, and more practical for clinical use [3638]. One recent device used three-dimensional columns of self-assembled super-paramagnetic beads that reach into a microfluidic channel to create an efficient sorting structure [37].…”
Section: Recent Developments In Magnetic Sensing and Actuationmentioning
confidence: 99%
“…A shrink induced magnetic trap is formed on a shape memory polymer and integrated into a microfluidic device to extract DNA samples for qPCR studies [7]. Imprinting technology is used to pattern magnetic microparticles on polymer substrates using a magnetic grid as the template.…”
Section: Introductionmentioning
confidence: 99%